POPULASI Pardosa sp. PADA HABITAT TANAMAN JAGUNG (Zea mays L.) KACANG TANAH (Arachis hypogaea), DAN TOMAT (Lycopersicum esculentum) DI KANONANG II KECAMATAN KAWANGKOAN BARAT - Marselina I. Kasibulan; Ventje Memah; Daysi Kandowangko (COCOS, 2017)
ABSTRACTTomato plants (Lycopersicum esculentum) are very important for human health because they contain high nutritional value. Corn is the second most important commodity crop after rice. Peanut (Arachis hypogaea L.) are economically the legumes are second only to soybeans. Spiders (Araneae) is a biological agent that is extremely potent in controlling insect pests in agricultural ecosystems. This research aims to study and know the population and the differences Pardosa sp. in the three habitat types, namely maize, peanuts and tomatoes.The research was done in Kawangkoan precisely in Kanonang II District West Kawangkoan ranging study was conducted in October-December 2016. At each location the garden area of research at all four corners given purpose tool trap traps for sampling, so that at the three locations the garden area there are four traps trap. So the total to trap traps is 12 pieces are used.Sampling is done once a week. Community composition of spider Pardosa sp. on each of the three types of habitat of agricultural crops that were collected there are 118 birds, which consisted of 39 tail number on average 4.87 maize, 32 head average number 4:00 in peanuts and 49 tail number on average 6:12 p tomato plants.